Pengaruh Media Pembelajaran Kahoot Berbasis Game Terhadap Motivasi Belajar Matematika Siswa Ditinjau Dari Gaya Belajar Impulsif dan Reflektif - Puja Suci Emilya, Puja; Putri, Rahmi (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2025)
lThis studyl aimsl to analyze lthe effectiveness lof using lKahoot lgame-basedl learningl media lin increasingl lstudents' mathematicsl learning motivation viewed from impulsive and reflective learning styles of grade VIII students at MTsN 1 Kerinci. This researchl employed lan experimentall method withl la Control Group Post Test-Only lDesign. lThe research samplel consisted lof 41 students divided into experimental classl (VIII A, 20 students) and control class (VIII D, 21 students) selectedl through lrandom lsampling. Research instrumentsl included llearning motivationl questionnaires and impulsive-reflective learning style questionnaires. Datal were analyzedl using independentl t-testl and ltwo-way lANOVA. The resultls showed significant differences in learning motivation between experimental and control groups (t_count = 4.523 > t_table = 2.023; p < 0.05). Students with impulsive learning styles demonstrated higher motivation improvement (mean = 78.45) compared to reflective students (mean = 74.32) when using Kahoot. Therel was al significant linteraction effectl between llearning medial land learning style (F = 6.847; p < 0.05). lThis study lconcludes that lKahoot is leffective in lincreasing mathematics llearning motivation, especially for students with impulsive learning styles.